2014
DOI: 10.4103/2045-080x.137540
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception of senior year pharmacy students about generic medicines in public Universities of Malaysia

Abstract: Objective:The aims of this study were to evaluate senior year pharmacy students' perceptions of and knowledge about generic medicines and generic substitution and to explore factors influencing these students' future generic substitution practices. Materials and Methods:The study was conducted among third year pharmacy students studying at five public pharmacy schools located in Malaysia. A pre-validated self-administered questionnaire was used to collect the data. The questionnaire was distributed via collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The overwhelming agreement by all final year undergraduate students in the three faculties that they needed more information on the quality and safety of generic medicines and that their healthcare training should include courses on national drug policy, essential medicine lists, and rational medicine use is a confirmation of their deficiency in knowledge and misconceptions about generic medicines. The use of an audio–visual educational package advocated in a Malaysian study [ 24 ] is also recommended to be adopted in the healthcare training institutions of Sierra Leone, as it is expected to critically appraise students about generics and their promotion in professional practice. Other educational interventions could include an interactive lecture that specifically covers topics such as bioequivalence, regulatory requirements for market authorization of generic medicine in Sierra Leone, generic medicine facts, and the promotion of rational prescribing and dispensing using generic medicines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming agreement by all final year undergraduate students in the three faculties that they needed more information on the quality and safety of generic medicines and that their healthcare training should include courses on national drug policy, essential medicine lists, and rational medicine use is a confirmation of their deficiency in knowledge and misconceptions about generic medicines. The use of an audio–visual educational package advocated in a Malaysian study [ 24 ] is also recommended to be adopted in the healthcare training institutions of Sierra Leone, as it is expected to critically appraise students about generics and their promotion in professional practice. Other educational interventions could include an interactive lecture that specifically covers topics such as bioequivalence, regulatory requirements for market authorization of generic medicine in Sierra Leone, generic medicine facts, and the promotion of rational prescribing and dispensing using generic medicines [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result in this study agreed with the finding reported by previous studies. [11][12] Moreover, Siam et al reported that there was a significant difference among pharmacy and medical students regarding knowledge of generic medicine in Bangladesh. [4] In contrast, a study conducted by Basak and Sathyanarayana in India showed that many of the pharmacists and drug retailers have misconception regarding generic medicines, and they lack enough knowledge about generic substitution, even if the prescribed medicines are not available.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the current literature suggests that pharmacy students have inadequate knowledge of generic medicines in several countries including Malaysia, Australia, Pakistan, Bangladesh and Afghanistan. [12][13][14][15][16] Therefore, the colleges of pharmacy in Yemen need to ensure that generic medicines are adequately covered in the pharmacy curriculum to prepare the future pharmacy practitioners with appropriate knowledge pertaining generic medicines, generic substitution, bioequivalence, bioavailability and related topics.…”
mentioning
confidence: 99%